EVALUATION EFFICIENCIES OF INHIBITORS IN THE INHIBITION OF REINFORCEMENT CORROSION IN REINFORCED CONCRETE - Aydin, Ozlem; Cizmecioglu, Zeki (YILDIZ TECHNICAL UNIV, 2013)
In this study, the effects of chloride in the formation of corrosion in concrete structures and efficiencies of inhibitors in the inhibition of reinforcement corrosion were evaluated. Corrosion of the steel causes the loss of the cross-section and can lead to reduced adherence between concrete and steel so corrosion can lead to reduced strength of reinforced concrete. Earthquake safety of structure is likely to deteriorate and completion of the service life of the structure is likely to come unusable due to corrosion. To minimize these problems need to take various measures against corrosion. Between existing methods, corrosion inhibitors can be presented primarily in order to prevent and stop the chloride induced corrosion as a simple and cost effective prevention technique.
Keywords: Reinforcement; inhibitor; corrosion; concrete; chloride; Engineering